Community Empowerment Through Cough Self-Medication Counseling And Utilization Of Herbal Medicines - Nurhikmah; Ibnu Imam Al Ayyubi; Eko Prayetno; Firda Noerzanah; Muhammad Rizal Asri (Jurnal Pengabdian Kepada Masyarakat, 2026)
This study explores the effectiveness of community empowerment through health education on self-medication for cough and the utilization of herbal remedies in Wawobeau Village, South Wawonii, Southeast Sulawesi. Using a Participatory Action Research (PAR) approach, this research emphasizes the active involvement of the local community in every stage of the empowerment process. The findings indicate that the education program significantly enhanced the community’s knowledge and skills in managing minor health issues, particularly coughs. Before the intervention, many individuals either ignored symptoms or relied on inappropriate treatments. However, after participating in the program, the community became more proactive in seeking proper solutions, whether through the correct practice of self-medication or the use of locally available herbal remedies. The participatory approach ensured that the information was not only received but also internalized and applied by the community, leading to behavioral changes. Overall, this study highlights the importance of community-based health education as a means of knowledge transfer and a tool for fostering collective awareness and responsibility in maintaining public health. The findings suggest that such initiatives contribute to improving the overall quality of life in the region.